EVALUATION OF THE RELIABILITY OF A TYPICAL PIER BRIDGE OF HSR JAKARTA-BANDUNG WITH DOUBLE SPHERICAL BEARING DUE TO EARTHQUAKE LOAD USING PROBABILITY APPROACH - ZAKIYYAH, AMIRAH
The reliability of the bridge structure needs to be calculated due to the uncertainty of earthquake loads and resistance in actual conditions. The random variable used in the reliability calculation is the earthquake load which is then used as the fragility curve as resistance and the Bandung City hazard curve as the load. The reliability of the structure is calculated using a probability approach, namely the total probability theorem. The quality of concrete and steel is also taken into account as a random variable in calculating the reliability of the bridge pier structure using the Monte Carlo simulation. The analysis was carried out on the tipical bridge structure of the Jakarta-Bandung High Speed Railway (HSR) using isolator, namely in the Bandung area and its surroundings. An analysis of the bridge structure without an isolator on the same structure was also carried out to see the effectiveness of the use of the isolator against the design earthquake. Non-linear Time History (NLTHA) analysis was carried out with 11 pairs of ground motions (motions) which were scaled to the response spectra of the target (Bandung City) using the amplitude scaling method using the Deep Soil program, while the overall structural analysis used the Midas Civil 2021 program. Incremental Dynamic Analysis (IDA) is only carried out on structures with isolator up to the isolator displacement limit, which is 300 mm as the definition of structural failure in accordance with the results of isolator tests in the laboratory. From the monte carlo simulation, the value of ? (safety index) of structures with isolator is 3.22 for the X direction and 5 for the Y direction. Meanwhile, the ? values for structures without isolator are 1.5 in the X direction and 0.715 in the Y direction. the Bandung City hazard curve equation and the value of ? is 2,415 in the X direction and 2,505 in the Y direction. The value of ? in the analysis of structural reliability with isolator obtained still does not meet the minimum value required by AASHTO of 3.